Open-source insect camera trap with vibrational detection and luring for monitoring Stictocephala basalis (Walker, Hemiptera: Membracidae: Smiliinae) - Vincent Vaughn; Andrew Ensinger; Edwin Harris; Elijah Shumway; Rachele Nieri; Vaughn Walton; John Selker; Chet Udell (HardwareX)
We have developed a novel device for automatic sensing, luring, and imaging insects that use substrate-borne vibrational signals for identifying and locating mating partners. The device is capable of measuring the activity patterns of these insects in a local area. It is intended to be used for monitoring pest insects; the current version of the device focuses on the treehopper species Stictocephala basalis (Walker, Hemiptera: Membracidae: Smiliinae) that may serve as a vector for Grapevine Red Blotch Disease. The device detects male treehoppers by sensing their mating calls using a piezoelectric contact microphone attached to a host plant, and lures them towards an imaging area by playing a prerecorded female mating call using a vibration exciter. This work is significant because previous efforts towards agricultural pest monitoring through biotremology methods has achieved only limited practical application. The trap has successfully detected and recorded wild treehopper mating calls and activity patterns, and it provides a pathway towards targeted, non-toxic pest control of various insect species that use vibrational communication. The system may be adapted to physically trap insects or alter damaging behavior in various cropping systems.